NUTRITIVE POTENTIAL AND PALATABILITY PREFERENCE OF BROWSE FOLIAGE BY LIVESTOCK IN ARID RANGELANDS OF CHOLISTAN DESERT (PAKISTAN) - M. Abdullah; M. Rafay; T. Hussain; H. Ahmad; U. Tahir; F. Rasheed; T. Ruby; S. Khalil (Journal of Animal and Plant Sciences, 2017)
This study was conducted in Cholistan rangelands to collect information about the palatability and nutritive potential of browses that remained available throughout the year for livestock. Results revealed that ten browse species consisting of seven shrubs and three trees were observed to have preference, accessibility and abundance for grazing animals. Based on palatability Prosopis cineraria and Acacia nilotica were highly palatable, Calligonum polygonoides, Suaeda fruticosa, Salsola baryosma, Haloxylon recurvum, Capparis decidua, Calotropis procera and Tamarix aphylla were moderately palatable whereas Haloxylon salicornicum was less palatable. Free grazing animals were consisting of mix herds of sheep, goat, cattle and camel. They preferred different plants and their parts like leaf, shoot, flower, and fruits. Forage quality assessment showed significant differences (p<0.05) in nutrient values among selected species. The mean values of dry matter, crude protein, ether extract, crude fiber, total ash, nitrogen free extract, neutral detergent fibers, acid detergent fibers, hemicellulose and acid detergent lignin were 93.58%, 11.54%, 1.87%, 4.36%, 13.44%, 48.79%, 40.17%, 23.47%, 16.70%, and 7.22%, respectively which indicate fair level of nutrients. Consequently, this preliminary study has shown that identified browses have good palatability and feed potential for ruminants in the arid rangelands of Cholistan desert.
Keywords: Animal feed; Browse species; Cholistan rangelands; Palatability; Nutritive value